Fabrication of flexible and self-standing inorganic-organic three phase magneto-dielectric PVDF based multiferroic nanocomposite films through a small loading of graphene oxide (GO) and Fe3O4 nanoparticles - Jayakumar, O D; Abdelhamid, Ehab H; Kotari, Vasundhara; Mandal, Balaji P; Rao, Rekha; Jagannath; Naik, Vaman M; Naik, Ratna; Tyagi, A K (Dalton transactions : an international journal of inorganic chemistry, 2015)
Flexible inorganic-organic magneto-electric (ME) nanocomposite films (PVDF, PVDF-GO, PVDF-Fe3O4 and PVDF-GO-Fe3O4), composed of well-dispersed graphene oxide (GO 5 wt%) and magnetic Fe3O4 nanoparticles (5 wt%) embedded into a poly(vinylidene-fluoride) (PVDF) matrix, have been prepared by a solvent casting route. The magnetic, ferroelectric, dielectric, magneto-dielectric (MD) coupling and structural properties of these films have been systematically investigated. Magnetic (Ms = 2.21 emu g(-1)) and ferroelectric (P = 0.065 μC cm(-2)) composite films of PVDF-GO-Fe3O4 (PVDF loaded with 5% GO and 5% Fe3O4) with an MD coupling of 0.02% at room temperature (RT) showed a three times higher dielectric constant than that of the pure PVDF film, with a dielectric loss as low as 0.6. However, the PVDF-Fe3O4 film, which exhibited improved magnetic (Ms = 2.5 emu g(-1)) and MD coupling (0.04%) properties at RT with a lower dielectric loss (0.3), exhibited decreased ferroelectric properties (P = 0.06 μC cm(-2)) and dielectric constant compared to the PVDF-GO-Fe3O4 film. MD coupling measurements carried out as a function of temperature on the multi-functional PVDF-GO-Fe3O4 film showed a systematic increase in MD values up to 100 K and a decrease thereafter. The observed magnetic, ferroelectric, dielectric, MD coupling and structural properties of the nanocomposite films are attributed to the homogeneous dispersion and good alignment of Fe3O4 nanoparticles and GO in the PVDF matrix along with a partial conversion of nonpolar α-phase PVDF to polar β-phase. The above multi-functionality of the composite films of PVDF-Fe3O4 and PVDF-GO-Fe3O4 paves the way for their application in smart multiferroic devices.